Faktor Psikologis Konsumen yang Memengaruhi Perilaku Pembelian Impulsif (Impulse Buying Tendency) Produk Fashion di Malang Town Square (Matos) - Riwoe, Yoan Wahyu Pricilia Dao; Zain, Djumillah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Phenomena that occur in today's society is a society tend to have properties consumer spending, which it is because people are less conscious of differences fulfillment of wants and needs. It is increasingly the case, because on the other hand some shopping centers have a concept of one stop shopping even easier for people to fulfill their shopping desires. Sedlian several factors above, there is also the factor of the man himself that influence their shopping behavior, these factors are affective and cognitive factors. Affective aspect itself is the emotional or impulse in man to satisfy their desires and needs without regard to risks, whereas cognitive factors are aspects of human beings who are still concerned with the logic and value of the product to be purchased. Second aspect is the psychological aspect in man, where man pick 4 key psychological factors, namely motivation, perception, learning, and memory. While greater affective aspects affect what happens is impulse buying behavior in which the purchase was made without much consideration. In this research emphasis on fashion products because it is a product that has a lot of variety and has a continually changes following the change of time, and performed at Malang Town Square, which is a shopping center shopping center and within easy driving distance from anywhere a shopping center located in a strategic location.Keywords : psychological factor, motivation, perception, learning, memory, impulse buying behavior